A concept and industrial testing of a superheated steam rotary dryer demonstrator: Cocurrent-triple pass design. Issue 4 (12th March 2019) - Chryat, Y.; Esteban-Decloux, M.; Labarde, C.; Romdhana, H.
ABSTRACT: This study aims to provide a pertinent demonstration of the feasibility of superheated steam drying (SHSD) at industrial demonstrator scale. The dryer is of co-current, direct contact, and triple pass rotary type. The dryer is designed to operate under pressure (up 2 bar abs.) and at high temperatures (up 600°C). Given the operating conditions of pressure and temperature, the control and the instrumentation of the dryer were the subjects of a special study to ensure safe tests and measurements. The demonstrator was manufactured and set-up on an industrial site. Drying experiments on pressed beet pulp are being carried out. At the end of this study, we hope to show first results to demonstrate the drying feasibility and also to provide relevant data concerning the operation of SHSD.